2007
DOI: 10.1121/1.2775871
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear shear wave interaction in soft solids

Abstract: This paper describes nonlinear shear wave experiments conducted in soft solids with transient elastography technique. The nonlinear solutions that theoretically account for plane and nonplane shear wave propagation are compared with experimental results. It is observed that the cubic nonlinearity implied in high amplitude transverse waves at f(0)=100 Hz results in the generation of odd harmonics 3f(0), 5f(0). In the case of the nonlinear interaction between two transverse waves at frequencies f(1) and f(2), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 17 publications
3
42
0
Order By: Relevance
“…Landau and Lifshitz 42 write the strain energy W 3 up to third order by including terms in I 3 , I 1 I 2 , and I 3 1 . There are 4 combinations of the invariants in the strain energy at the fourth order: I 1 I 3 ; I 2 1 I 2 , I 2 2 , and I 4 1 , thus the fourth-order strain energy is 36,[43][44][45] …”
Section: Appendix: Fourth Order Elasticity Theorymentioning
confidence: 99%
“…Landau and Lifshitz 42 write the strain energy W 3 up to third order by including terms in I 3 , I 1 I 2 , and I 3 1 . There are 4 combinations of the invariants in the strain energy at the fourth order: I 1 I 3 ; I 2 1 I 2 , I 2 2 , and I 4 1 , thus the fourth-order strain energy is 36,[43][44][45] …”
Section: Appendix: Fourth Order Elasticity Theorymentioning
confidence: 99%
“…Porubov and Maugin [12] applied nonlinear strain waves to study the growth of long bones. Jacob et al [13] conducted nonlinear shear wave experiments in soft solids with the transient elastography technique. Zabolotskaya et al [14] showed that the material model in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Transient elastography is one of the most efficient approaches, as it images in real-time the transient propagation of shear waves in soft media using ultrafast echographic scanners. Based on this concept, there are three possible ways to quantify nonlinearity in soft solids: propagation of shock shear waves [1], nonlinear interaction between shear waves [2] and acoustoelasticity [3]. In a recent paper, shear wave propagation theory in soft solids brought new ideas in the field of elasticity theory.…”
Section: Introductionmentioning
confidence: 99%